Integration of experience based decision support in industrial processes - Rakoto, H.; Hermosillo-Worley, Jorge; Ruet, M. (My University, 2002)
This research alms at presenting the first elements of a study carried out in conjunction with Alstom Transport on the "Experience Feedback" and "Lesson Learned" problematic. The paper is divided in three sections. The first section presents the Experience Feedback process and problematic in Alstom. In order to solve this problematic, we propose in the second section a dedicated model and methodology for a rational implementation and choice of decision support in the Experience Feedback process. Finally, the third section concerns the exploitation of Experience Feedback in operational processes describing the way to retrieve past experiences according to its similarity with current situation.